Challenges in Treating Malignancies in HIV in Nigeria - Akinwande, Oluyemisi (2009)
PURPOSE OF REVIEW: Sub-Saharan Africa has the largest population of people living with AIDS in the world with Nigeria having the third largest after South Africa and India. With the advent of treatment programs, more people in Nigeria are now living with the virus but are at increased risk of cancer similar to the experience in other parts of the world. This review uses publications on HIV associated cancers emanating from Nigeria in 2008 to map the current landscape of prevention, diagnosis and treatment of these conditions. The opportunities and challenges identified in this review will provide a template for designing appropriate clinical and public health intervention to stem another epidemic, this time of AIDS associated malignancies. RECENT FINDINGS: There is a paucity of literature on AIDS associated cancers from Nigeria and most reports are based on hospital or pathology case series. Poor case identification and diagnosis, and rudimentary cancer registration militate against adequate quantification of the prevalence of AIDS associated cancers in Nigeria. Several initiatives, working with the HIV treatment programs, governmental and non-governmental local and international agencies are rising to the challenge and creating new opportunities for cancer prevention, treatment and research that takes advantage of improved treatment infrastructure provided for PLWA. SUMMARY: Nigeria is about to witness substantial increase in the background incidence of cancers due to high prevalence of HIV and expanded treatment programs. Creative methods are needed to deploy effective prevention, case identification, registration and treatment programs that are consistent with the socio-economic development of the country.